Management of tetralogy of Fallot in the pediatric intensive care unit - Owen Hammett; Owen Hammett; Michael J. Griksaitis; Michael J. Griksaitis (Frontiers Media S.A., 2023)
Tetralogy of Fallot (ToF) is one of the most common congenital cyanotic heart lesions and can present to a variety of health care professionals, including teams working in pediatric intensive care. Pediatric intensive care teams may care for a child with ToF pre-operatively, peri-operatively, and post-operatively. Each stage of management presents its own unique challenges. In this paper we discuss the role of pediatric intensive care in each stage of management.